Business Strategy and Competitive Advantage Nexus Among Landscape Business in Beijing, China - Liu, Jianling; Ani, Teodorica G. (International Journal of Global Economics and Management, 2024)
The study aims to determine the effectiveness of business strategy and its effect to competitive advantage of landscape business in Beijing, China. The objectives of the study seek to determine the extent of the competitive advantage of the landscape firms in terms of cost, flexibility, delivery, and quality. This also determine the effectiveness of the business strategies of the companies with regards to arenas, differentiators, vehicles, staging, and economic logic. The study proposed a strategic business toolkit guide for landscape business. The study utilized descriptive research method. This study conducted a survey among 139 general managers of landscape design companies in Beijing. To ensure sample representativeness, the study employed simple random sampling, selecting every general manager, through the wheel of names application, from the 237 companies, resulting in 139 valid responses. Frequency, percentage, mean and multiple regression, quantile regression analyses, Kruskal wallis, and ANOVA were finally used in this study. The study revealed that most of the landscape firms are corporation, with 1-10 employees, and with 1-3 years in business while majority have non-EPC contract. Landscape firms have highly competitive advantage with regards to flexibility, delivery, and quality while average competitive advantage in terms of cost. Landscape firms have effective business strategies in terms of arenas, differentiators, vehicles, staging, and economic logic. Business strategy has significant effect to competitive advantage of landscape firms in terms of cost, delivery, and quality but no effect on flexibility. There is no significant difference on the assessment of the respondents when grouped according to profile. The study proposed a strategic business toolkit guide for landscape firms in Beijing, China.